The value of transactional data to a consumer spending survey. - Erhard, Laura (Monthly Labor Review, 2026)
This article evaluates the potential use of transactional credit and debit card data, provided by the nonprofit Opportunity Insights, to complement the U.S. Bureau of Labor Statistics’ (BLS) Consumer Expenditure Surveys (CE), which measure household spending by type of good or service. The analysis compares month-to-month spending changes from January 2019 to December 2021 across broad industry categories, finding that transactional data trends align closely with CE data in sectors like food, accommodation, and entertainment, but show lower correlation and greater volatility in others such as information and telecommunication. Key challenges include differences in data organization—transactional data are categorized by merchant type rather than specific goods or services—and the lack of demographic detail and full representativeness in transactional data. Consequently, while transactional data may help identify emerging consumer spending trends and provide more timely preliminary estimates, the study concludes that these data cannot replace CE data for official statistics due to inherent comparability and coverage limitations.